2013
DOI: 10.1371/journal.pone.0072714
|View full text |Cite
|
Sign up to set email alerts
|

Are Bisphosphonates Effective in the Treatment of Osteoarthritis Pain? A Meta-Analysis and Systematic Review

Abstract: ObjectiveOsteoarthritis (OA) is the most common form of arthritis worldwide. Pain and reduced function are the main symptoms in this prevalent disease. There are currently no treatments for OA that modify disease progression; therefore analgesic drugs and joint replacement for larger joints are the standard of care. In light of several recent studies reporting the use of bisphosphonates for OA treatment, our work aimed to evaluate published literature to assess the effectiveness of bisphosphonates in OA treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 34 publications
1
51
3
1
Order By: Relevance
“…Bisphosphonates target bone remodelling and can therefore reduce BMLs 35. Animal studies have shown conflicting evidence on whether bisphosphonates are preventing cartilage damage,40 41 and there is a lack of long-term data on OA joint structure modification postbisphosphonate therapy 42. The effect of bisphosphonates on structural progression in humans has been explored in one observational study only, showing a trend towards a beneficial effect that was not statistically significant 43.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates target bone remodelling and can therefore reduce BMLs 35. Animal studies have shown conflicting evidence on whether bisphosphonates are preventing cartilage damage,40 41 and there is a lack of long-term data on OA joint structure modification postbisphosphonate therapy 42. The effect of bisphosphonates on structural progression in humans has been explored in one observational study only, showing a trend towards a beneficial effect that was not statistically significant 43.…”
Section: Discussionmentioning
confidence: 99%
“…However, in humans, two randomised controlled trials of risedronate for knee OA failed to demonstrate a significant reduction in JSN over time, 78,79 and similarly a recent systematic review concluded that there was limited evidence that bisphosphonates are an effective treatment option for pain in OA. 80 Following these negative studies, there has been a recent resurgence of interest in manipulating bone turnover for the treatment of OA following the publication of the SEKOIA trial of strontium ranelate for the treatment of knee OA. 81 This mixedgender, multicentre study demonstrated a reduction in the progression of JSN in the treatment group over a 3-year period, 81 and as such it has been heralded as the first positive Osteoarthritis and bone mineral density SA Hardcastle et al disease-modifying OA drug trial.…”
Section: Mechanisms Including Recent Insights From Genetic Studiesmentioning
confidence: 99%
“…intravenous clodronate in the treatment of hand OA with beneficial outcome for pain in their study [41]. However, a recent meta-analysis by our group did not show overall significant benefit overall for pain and function after use of bisphosphonates across several phenotype of OA, including hip, knee and hand [42]. Future studies targeted at specific stages of disease with proven synovitis and bone marrow lesions may be more helpful in establishing the potential future therapeutic use of bone-modulating agents in the clinic.…”
Section: Treatments For Hand Osteoarthritismentioning
confidence: 82%